2014
DOI: 10.1039/c4ra01795a
|View full text |Cite
|
Sign up to set email alerts
|

WS2 nanoparticles – potential replacement for ZDDP and friction modifier additives

Abstract: SummaryIn high-pressure, high-temperature sliding contacts, WS 2 nanoadditives react with the metal substrate to generate 100+ nm chemical tribofilms with a layered structure and excellent tribological properties. The friction, wear and micromechanical properties of WS 2 tribofilms are compared with those of tribofilms formed by the zinc dialkyldithiophosphate (ZDDP) antiwear additive and ZDDP-organic friction modifier (OFM) mixture. Nanoindentation measurements showed that WS 2 generates tribofilms with highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…34,43,46 The reason lies in the ability of TMD nanoparticles for forming complex tribofilms formed by exfoliated TMD lamellas accompanied with the presence of iron sulfides that form at the contact interface with superb tribological properties. 32,46 These kinds of tribofilms can also be formed by TMD nanotubes under the presence of lubricant additives in model oils. 34 Hence, we aim to show the feasibility of applying the in situ sulfurization of MoO 3 nanotubes in sliding contacts using severe contact conditions.…”
Section: In Situ Tribochemical Sulfurization Under Extreme Pressure Cmentioning
confidence: 99%
See 1 more Smart Citation
“…34,43,46 The reason lies in the ability of TMD nanoparticles for forming complex tribofilms formed by exfoliated TMD lamellas accompanied with the presence of iron sulfides that form at the contact interface with superb tribological properties. 32,46 These kinds of tribofilms can also be formed by TMD nanotubes under the presence of lubricant additives in model oils. 34 Hence, we aim to show the feasibility of applying the in situ sulfurization of MoO 3 nanotubes in sliding contacts using severe contact conditions.…”
Section: In Situ Tribochemical Sulfurization Under Extreme Pressure Cmentioning
confidence: 99%
“…The latter condition is nowadays already fulfilled by most of the common commercially available lubricants, since they contain anti-wear additives such as zinc dialkyl dithiophosphate (ZDDP) or extreme pressure additives, such as sulfurized olefins. 32 The aim of this work is to promote the in situ sulfurization of molybdenum oxide nanotubes using conventional sulfurcontaining lubricant additives such as a ZDDP anti-wear additive and a sulfurized-olefin extreme pressure additive. The approach is verified giving special emphasis to the role of the additive chemistry and contact conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nanoparticles have been considered as friction modifiers and antiwear additives [1][2][3][4][5][6][7][8][9][10][11][12]. Studies have shown that the addition of nanoparticles to base stock lubricating oil can reduce friction and wear and have concluded that nanoparticles might be beneficial lubricant additives, even though some might be hard and could be abrasive [1,2,[4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Various hypotheses have been offered about how nanoparticles reduce friction and wear. These include the ball-bearing or rolling effect [2], the formation and removal of layered-structure protective tribofilms [3], penetration into the rubbing surfaces that, in turn, changes the material properties at the contact points between mating surfaces (the "mending effect") [13], and the polishing effect [2]. Most of the evidence found in the open literature was collected from tests performed under laboratory conditions and may not indicate whether the benefits will occur under conditions experienced in an actual engine.…”
Section: Introductionmentioning
confidence: 99%
“…By covering organic chains on the surface of inorganic nanoparticles, the dispersity and stability of inorganic nanoparticles in organic solvent would increase significantly, especially in lubricants. Varieties of nanoparticles, such as TiO 2 [5,6], CuO [7,8], ZnO [9], Fe 3 O 4 [10], Sn [11], and WS 2 [12], were added to lubricants as additives and those nanoparticles exhibit good tribological performances. Among these nanoparticles, silica nanoparticles are particularly attractive because of their good environmental compatibility, low cost, and excellent tribological performance.…”
Section: Introductionmentioning
confidence: 99%